PENGARUH PERASAN DAUN SURUHAN (Peperomia pellucida) TERHADAP MORTALITAS Aedes aegypti - Nuzlan Rasjid; Aryati Abdul; Mustamin Ibrahim (Fakultas MIPA Universitas Negeri Gorontalo, 2020)
The research aimed to find out the effect of suruhan (Peperomia pellucida) leaves extract to the mortality of Aedes aegypti. The method applied in this research was laboratory experiments.The research was conducted in Zoology Laboratory of Department of Biology, State University of Gorontalo, from August to September 2019. The research employed Completely Randomized Design (CRD) through 4 treatments namely 0%, 15%, 20%, and 25%, as well as 3 replications. In Addition, every treatment involved 10-second instar larvae of Aedes aegypti as test animal. The ANAVA F-Test analysis was to find out the effect of treatment to mortality of Aedes aegypti and LSD (Least Significant Difference) analysis was to find out difference of every treatment. The mortality of Aedes aegypti was not found at concentration 0%, the mortality of Aedes aegypti with average 2,33 animals were found at concentration 15%, the mortality of Aedes aegypti with average 5,00 animals were found at concentration 20%, and the mortality of Aedes aegypti with average 6,67 animals were found at concentration 25%. In addition, the ANAVA F-Test analysis revealed effect of treatment to mortality of Aedes aegypti (p